2018
DOI: 10.1016/j.addr.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mucus models to evaluate the diffusion of drugs and particles

Abstract: Mucus is a complex hydrogel that acts as a natural barrier to drug delivery at different mucosal surfaces including the respiratory, gastrointestinal, and vaginal tracts. To elucidate the role mucus plays in drug delivery, different in vitro, in vivo, and ex vivo mucus models and techniques have been utilized. Drug and drug carrier diffusion can be studied using various techniques in either isolated mucus gels or mucus present on cell cultures and tissues. The species, age, and potential disease state of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 232 publications
(302 reference statements)
0
119
0
Order By: Relevance
“…The topological organization of MUC6 oligomers is probably of importance for the permeability of gastric mucus. This might also influence the absorption of nutrients and drug delivery . Furthermore, TFF2 together with MUC6 might also be involved in the phenomenon of “viscous fingering”, which is observed if hydrochloric acid penetrates gastric mucus .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topological organization of MUC6 oligomers is probably of importance for the permeability of gastric mucus. This might also influence the absorption of nutrients and drug delivery . Furthermore, TFF2 together with MUC6 might also be involved in the phenomenon of “viscous fingering”, which is observed if hydrochloric acid penetrates gastric mucus .…”
Section: Resultsmentioning
confidence: 99%
“…We have investigated for the first time two different commercial porcine gastric mucin preparations for their TFF2 contents. In the past, they were extensively studied as model systems to understand the microstructure and complex rheology of gastric mucus . Furthermore, one preparation is also sold as a saliva substitute .…”
Section: Introductionmentioning
confidence: 99%
“…Veres concluded that inhaled environmental allergens may induce aberrant activation of immune cells in the airway mucosa, resulting in allergic airway disease. Studies of the side effects of drug delivery have also shown that penetration of particulates through mucus poses a potential risk to human health . Nanocarriers are normally used in drug delivery because they can penetrate quickly through mucus to reach the underlying cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our model did not include goblet cells, mucus secretory cells, or submucosal glands to produce mucosal lining fluid (ie, mucus) . Mucin is the main structural component of mucus; these components interact with each other and with other components of mucus to form a meshlike structure . In addition to this meshlike structure, mucus captures foreign particles via an adhesion effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation